2019
DOI: 10.1213/ane.0000000000003385
|View full text |Cite
|
Sign up to set email alerts
|

Trainability of Cricoid Pressure Force Application: A Simulation-Based Study

Abstract: At baseline, performance was poor at achieving target forces specified by national guidelines. Simulation-based training improved the success rate, but no participant achieved the predefined threshold for proficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Cricoid force when applied blind exceeded cricoid force applied with the use of biofeedback sensor by a mean of 6-8 Newtons. We feel that this difference is of clinical importance, most clinical studies evaluating cricoid pressure had used a difference of 5 Newtons as an acceptable window [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cricoid force when applied blind exceeded cricoid force applied with the use of biofeedback sensor by a mean of 6-8 Newtons. We feel that this difference is of clinical importance, most clinical studies evaluating cricoid pressure had used a difference of 5 Newtons as an acceptable window [20].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, even with the knowledge of the cricoid force range, it may not be easy to conceptualize force in Newtons and then translate it into practice. Relying on experience in applying the correct force is not reliable as studies had showed no correlation between performance with work experience or profession, rather, strength and dexterity may play a more important role [20,21,24]. Lastly, the consequence of inappropriate application of cricoid pressure is detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover several important disadvantages of cricoid pressure were observed: a higher incidence of Cormack-Lehane grade 3-4, a more difficult mask ventilation, a more difficult laryngeal mask insertion, a decreased lower esophageal sphincter tone and a more frequent gag reflex and higher incidence of vomiting 43 . Additionally, teaching the right practice of cricoid pressure remains impossible: neither anesthesiologists nor nurses can be trained to apply a pressure of 10 + 5 N and 30 + 5 N in a training model 46 . Furthermore, in clinical practice, even with the feedback of real-time measurements, it is biomechanically impossible to achieve 30 N cricoid pressure during the counter force of laryngoscopy 47 .…”
Section: Cricoid Pressure During Rapid Sequence Inductionmentioning
confidence: 99%
“…Da der Krikoiddruck im Alltag selten angewandt wird, ist es wichtig, die Anwendung zu trainieren, da sich so deutlich bessere Erfolgsraten abzeichnen [29].…”
Section: Pr a Xisunclassified